Legal Protection of Rights - Child Labor Rights for Violating Employment Requirements Practices (Study at Cigarette and Incense Factory, Wagir District, Malang Regency) - Trimahayati S.W. (Trigin Publisher, 2022)
In writing this thesis, the writer discusses the issue of Legal Protection of Child Labor Rights for Violating Employment Requirements Practices. This is motivated by the most basic child problem and much highlighted by related parties is the problem of child labour. Until now, the number of child laborers has not been recorded with certainty. Child labor is spread both in rural and urban areas. According to the chairman of the Community Potential Development Foundation, Adi Eko Warsono, there were at least 1,883 child workers in Malang Regency. This number is expected to continue to increase. Data collected from the Wagir, Tumpang and Pakis sub-districts shows that on average 50 percent of the children are working, with the youngest being 7 years old and the oldest being 18 years old. In Dalisodo Village, Wagir District, for example, the percentage of working children is quite high. Of the 471 children aged 7 to 18 years, 339 of them were already working. Most of them work in factories. In writing thesis, to simplify and understand the problems discussed, the authors use an empirical juridical approach. Then the data is processed and analyzed descriptively. Based on the results of the research, the authors obtained answers to existing problems, namely: the form or characteristics of violations of these work requirements including verbal parental consent, absence of agreement between parents and employers, long working hours, wages that do not comply with the Malang Regency Minimum Wage , occupational health and workplace conditions are not guaranteed.